Dixmier traces on noncompact isospectral deformations - Gayral, Victor (2006)
We extend the isospectral deformations of Connes, Landi and Dubois-Violette to the case of Riemannian spin manifolds carrying a proper action of the noncompact abelian group R^l. Under deformation by a torus action, a standard formula relates Dixmier traces of measurable operators to integrals of functions on the manifold. We show that this relation persists for actions of R^l, under mild restrictions on the geometry of the manifold which guarantee the Dixmier traceability of those operators.